Taking On Unexpected Leadership Roles - Alicia Domack (Academic Chairpersons Conference Proceedings, 2017)
Leaders are occasionally asked to take on new roles with very little notice. This session will present new chairs with some concrete tips to help individuals taking on unexpected leadership roles survive and eventually thrive in the position.
Keywords: new leadership; mentorship; building relationships